Uji Aktivitas Antibakteri dan Sifat Fisik Gel Ekstrak Temulawak Terhadap Staphylococcus Aureus ATCC 25923 - Maulana Nugraha; Ferli Eko K (Jurnal Farmasi Indonesia, 2024)
Temulawak (Curcuma zanthorrhiza) can be used as a traditional medicine. The use of temulawak directly on the skin is impractical and uncomfortable, so it is formulated in an emulgel dosage form. The test material is Temulawak powder extracted by maceration method with 96% ethanol solvent. The viscous extract of emulgel preparation and physical properties tested includes organoleptic, spreadability. Adhesion and pH. Antibacterial activity test against Staphylococcus aureus was carried out by using the well method. Antibacterial activity is indicated by the presence of an inhibitory zone on the emulgel with a concentration of 5%, 10% and 15%. The test results of the physical properties of Temulawak extract emulgel have good organoleptic, adhesion and pH, but the spreadability does not meet the good spreadability standards, because the diameter requirements for good dispersion for emulgel are 5 to 7 cm. And the results of the antibacterial activity test showed that the emulgel from Temulawak extract had antibacterial activity against Staphylocuccus aureus at concentrations of 5%, 10%, and 15%. With mean values of 15 mm, 17 mm and 19 mm, respectively. These results indicate that the Temulawak extract emulgel has antibacterial activity against Staphylococcus